Cereal breakfast foods - Haggart, Margaret Helen (My University, 1905)
Introduction: Within a few years various cereal products, which are called Breakfast Foods have been placed on the market. These are manufactured from wheat, corn, oats and rice and in the making are said to undergo various secret processes. The first breakfast food was “porridge” which was made by boiling coarsely ground wheat or oats. This was used chiefly by the people of the British Isles. These people subjected this oat or wheat meal to prolonged cooking, it being a historical fact that the porridge pot was always on the stove. It constituted their main article of food and with milk it formed a balanced dietary. When some of these people immigrated to this country, they introduced their food here. Finding little wheat of oats and learning to use corn, they substituted coarsely ground corn for the basis of their porridge. They knew by experience that these coarsely ground cereals were more palatable after prolonged cooking and this unintentionally increased their digestibility. Manufacture. With improved methods along all lines, the attention of the manufacturers has been called to the possibilities of cereal preparations. With the desire for shorter methods and quicker results, which everywhere permeates American life, the production of prepared.
Citation: Haggart, Margaret Helen. Cereal breakfast foods. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Diastatic Enzymes; Chemical Analyses of Breakfast Cereals; Digesting Raw Starch; Theses